The Effect of Emotional Intelligence and Locus of Control on Ethical Behavior of Educator Accountants at Private Universities in North Sumatra - Fitriani Saragih; Novien Rialdy; Edisah Putra Nainggolan (Journal of International Conference Proceedings, 2022)
Ethical behavior is defined as behaving in a way that meets the expectations of society as a whole when it comes to doing what is right and good. Ethical behavior can have a positive impact on the quality of individuals who are influenced by external factors. By living by principled values, these individuals can develop healthy behavioral patterns. The purpose of this study was to determine the effect of emotional intelligence and locus of control on the ethical behavior of educator accountants at private universities in North Sumatra. All of the accounting professors that instruct at private universities in North Sumatra made up the study's population. While there were 206 educator accountants included in the study's sample size. Data is gathered through surveys and interviews, and multiple linear regression is utilized to evaluate it. The findings revealed that there is a significant influence of emotional intelligence and locus of control on the Ethical Behavior of Educator Accountants at private colleges in North Sumatra.